ILUMINAÇÃO DOS MORTOS: Uma fotofabulação Afro-pindorâma na Amazônia paraense a partir dos acervos da família Jinknss e Castro em contraponto aos carte de visite etnográficos do século XIX - CASTRO, Naiara Jinknss de (Universidade Federal do Pará, 2025)
This research aims to create “photofabulations” to fill gaps and recover the memories and histories of Afro-Pindoramic people through photography. As practice-based research, I developed the concept of “Photofabulation” as an artistic practice that emerges for the study and reinterpretation of the XIX century’s carte de visite. Therefore, I challenge and fictionalize the carte de visite created by foreign photographers in Brazil throughout the XIX century that contributed to a history of violence, stereotypes, and one-sided histories regarding the Afro Pindoramic population. I elaborate this process in order to understand how racial stigmas that are present in these cartes de visite have impacted the development of my identity and the history of my family. To reach this proposal, I have created digital interventions in my family’s photo albums aiming to evoke, complement, recognize, and restore the absences generated through the widespread reproduction of the carte de visite. While reflecting upon these images and integrating them into the histories of my family, I hope to establish a more sensible relationship with the past and the memories of my own family’s histories. This research’s methodology includes: a literature review on the concept of Critical Fabulation; digital interventions in images of historical archives; and the digital merging of my family’s (Jinknss and Castro) photo albums. I hope to contribute to the development of artistic counter-narratives that value and represent the experiences and knowledge of Afro-Pindoramic populations in Brazil, exposing an array of complexities that compose of the identity, diversity and history of the country, thus promoting a richer and more inclusive comprehension of Brazilian society.